Nano-encapsulated Ajwain essential oil elicits resistance against early blight in tomatoes (Solanum lycopersicum L.): Tomato resistance to early blight by natural elicitors - Izadi, Mahin; Jorf, S. Ali Moosawi; Nowroozi, Ghazal; Sedghi, Mohammad; Naseriyeh, Tahereh; Rahmani, Shokofeh; Fathi, Jafar; Kahrizi, Danial (Cellular and Molecular Biology, 2025)
Early blight, caused by Alternaria alternata, poses a significant threat to tomato production worldwide. This study investigates the potential of nano-encapsulated ajwain (Trachyspermum copticum) essential oil, delivered via chitosan nanoparticles, to induce systemic resistance in tomato plants against early blight. Oxidative stress, measured by malondialdehyde content, was significantly reduced in plants treated with nano-encapsulated Ajwain essential oil compared to controls. Furthermore, the activity of antioxidant enzymes (SOD, CAT, and POD) was significantly elevated in treated plants, indicating an enhanced defense response. The nano-encapsulated essential oil demonstrated superior efficacy in controlling early blight symptoms. These results suggest that chitosan nanoparticle-mediated delivery of ajwain essential oil is a promising, environmentally friendly strategy for enhancing tomato resistance to early blight.